In control at 50+ : how to succeed in the new world of work - Hannon, Kerry (Ascent Audio, 2022)
Anyone who began working twenty or thirty years ago has witnessed astonishing changes in the workplace during their career. When the global pandemic hit, older workers fortunate enough to retain their jobs once again had to navigate enormous upheaval, virtually overnight. Working from home, often in isolation, over-fifties found themselves facing daunting technological and social challenges. If this scenario is all too familiar, In Control at 50+ shows how to make the new normal work for you. Kerry Hannon, a workplace futurist and renowned expert on business, careers, and personal finance, combines all her insights and skills to help you actively shape your work future into what you want it to be. Hannon illustrates how COVID-19 changed the nature of work, provides a compellingly optimistic vision of the future, and highlights opportunities and specific action steps for achieving success, including how to: develop a positive mindset about your career and financial future; create a powerful resume and a great online presence; master the virtual interview process; strategically manage remote work to benefit your career; and make a successful career transition to something more exciting and rewarding. In Control at 50+ also provides winning advice specifically tailored for women, many of whose careers were uniquely affected by COVID-19.